Targeting the hydrophobic pocket of autotaxin with virtual screening of inhibitors identifies a common aromatic sulfonamide structural motif. (15th January 2014) - Fells, James I.; Lee, Sue Chin; Norman, Derek D.; Tsukahara, Ryoko; Kirby, Jason R.; Nelson, Sandra; Seibel, William; Papoian, Ruben; Patil, Renukadevi; Miller, Duane D.; Parrill, Abby L.; Pham, Truc‐Chi; et al.
<x xml:space="preserve">Abstract</x> Modulation of autotaxin (ATX), the lysophospholipase D enzyme that produces lysophosphatidic acid, with small‐molecule inhibitors is a promising strategy for blocking the ATX–lysophosphatidic acid signaling axis. Although discovery campaigns have been successful in identifying ATX inhibitors, many of the reported inhibitors target the catalytic cleft of ATX. A recent study provided evidence for an additional inhibitory surface in the hydrophobic binding pocket of ATX, confirming prior studies that relied on enzyme kinetics and differential inhibition of substrates varying in size. Multiple hits from previous high‐throughput screening for ATX inhibitors were obtained with aromatic sulfonamide derivatives interacting with the hydrophobic pocket. Here, we describe the development of a ligand‐based strategy and its application in virtual screening, which yielded novel high‐potency inhibitors that target the hydrophobic pocket of ATX. Characterization of the structure–activity relationship of these new inhibitors forms the foundation of a new pharmacophore model of the hydrophobic pocket of ATX.